Pilot plant study on ultrafiltration of POME - Mohd. Saleh Suwandi ,; Anhar Suki, (1989)
Pilot plant study on ultrafiltration of Palm Oil Mill Effluent (POME) was performed at United Plantation Palm Oil Mill, Jenderata Estate, Perak, Malaysia. Industrial thin channel DDS35-2.25 was utilized to house two kinds of membranes, polysulfone GR61P and skinned polyamide membranes. Long term flux decline and method of cleaning the membranes were investigated. The experiments were design to study a three stage ultrafiltration process which involved three different concentration. The concentration in each stage was determined by considering the minimum membrane area required for a five fold increase in concentration at the final stage. Unless stated the experiments were performed at 60 °C and a pressure of about 1. 2 bars